2012
DOI: 10.1177/1079063212464660
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Sexual Associations in Contact and Noncontact Child Sex Offenders Using the Single Category – Implicit Association Test

Abstract: Previous studies found associations between children and sex in child sex offenders (CSOs) using the Implicit Association Test (IAT). We used a modification of this task, the Single Category-Implicit Association Test (SC-IAT) to unravel child-sex associations in CSOs. Using the SC-IAT, we were able to test whether CSOs indeed hold stronger child-sex associations relative to adult-sex associations, compared to adult sex offenders and nonoffenders. Furthermore, we examined whether contact CSOs differed from nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…This uses a similar procedure as the original IAT but differs in that only one target category is used. The reliability and validity of the ST-IAT has previously been supported (Bluemke & Friese, 2008;Conroy, Hyde, Doerksen, & Riberio, 2010;Hempell, Buck, Goesthals, & van Marle, 2012;Wilson & Scior, 2015). In the current study, split-half coefficients (.76) and Cronbach's alpha values using D scores (α=.82) demonstrated reliability.…”
Section: Implicit Attitudesmentioning
confidence: 86%
“…This uses a similar procedure as the original IAT but differs in that only one target category is used. The reliability and validity of the ST-IAT has previously been supported (Bluemke & Friese, 2008;Conroy, Hyde, Doerksen, & Riberio, 2010;Hempell, Buck, Goesthals, & van Marle, 2012;Wilson & Scior, 2015). In the current study, split-half coefficients (.76) and Cronbach's alpha values using D scores (α=.82) demonstrated reliability.…”
Section: Implicit Attitudesmentioning
confidence: 86%
“…The IAT has good predictive validity in various domains of psychopathology (Roefs et al, 2011) and is relatively resistant to deliberate faking (Cvencek, Greenwald, Brown, Gray, & Snowden, 2010; Steffens, 2004). Moreover, previous studies have successfully demonstrated the ability of the IAT to accurately characterize the sexual interest of child abusers; results indicate that child abusers more strongly associate “children” and “sex” (or “sexual” or “sexy”) than do other types of offenders (Gray, Brown, MacCulloch, Smith, & Snowden, 2005; Hempel, Buck, Goethals, & van Marle, 2013; Nunes, Firestone, & Baldwin, 2007; Steffens, Yundina, & Panning, 2008). Brown, Gray, and Snowden (2009) even showed that child–sex associations can be used to reliably distinguish pedophilic offenders (who victimize children <12 years of age) from hebephilic offenders (who victimize youths aged 12-15 years).…”
Section: Introductionmentioning
confidence: 92%
“…Eckhardt et al, 2012;Gray, Brown, MacCulloch, Smith, & Snowden, 2005;Hempel, Buck, Goethals, & van Marle, 2013;Kanters et al, 2014;Snowden et al, 2004;Van Leeuwen et al, 2013). During this computerized task, patients have to assign target stimuli (either a word or a picture) as quickly as possible to the appropriate target by pressing a left or a right button.…”
Section: Implicit Associationsmentioning
confidence: 99%